Teaching Writing for L2 writers in Indonesia and Teaching Writing for L1 writers in the U.S : A Reflection of An Indonesian Graduate Teaching Assistant in First-Year Composition course - Sutrisno, Dwi Budidarma (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2024)
This study is conducted in order to obtain a reflection from Andy (pseudonym) an Indonesian graduate teaching assistant currently serving at one of the American public universities in Arizona about the experience of teaching writing for L2 writers in Indonesia and teaching writing for L1 writers in the U.S. The study is framed in a narrative inquiry investigation using three stages of open-ended and closed-ended interview questions then the data went through narrative analysis based on the data collected from the participant. This current study focuses on Andy’s reflection on his teacher experience, teacher beliefs & attitudes and teacher knowledge. The study found that for teacher experience Andy has significant teaching experience between teaching in the U.S compared to teaching in Indonesia, while for teacher teacher beliefs and attitude Andy has shifted his pedagogical beliefs and attitudes, as for teacher knowledge Andy has showcased specific subject matter knowledge about teaching writing in FYC course.